Improving English Vocabulary Mastery by Using the Alphabet Game for Class VIII at Junior High School Metro TMI RQ Metro - Pauliana, Riska; Suhono, Suhono; Pratiwi, Wiwied; Sari, Yeasy Agustina (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2023)
The students was the lack of enthusiasm for English learning. Students sometimes get bored in learning process. The purpose of this research was to improve how to get well students at SMP TMI RQ Metro in acquire English vocabulary material for class VIII A. The researchers used classroom action research, either in Cycle I and Cycle II. Data was collected through observation, interviews, tests and documentation. The result showed that 9 out of 20 students passed with a percentage of 45% in the observation cycle I. 11 students with a completeness level of 55% were students who did not complete. with an average value of 70.75. Hence, the classical completeness of the first cycle is 45%. It was observed that 80% of 20 students, 16 of which completed it during the second cycle. Four students with a 20% completion rate did not complete the course. with an average of 80 points. As a result, a typical cycle II is 80% complete. In other words, the results of the second cycle of observations succeeded in obtaining the KKM score that had been determined by the school and the completeness of the learning objectives for students.Keywords: Student Learning Outcomes, Vocabulary Material, Alphabet Games